2004
DOI: 10.1016/j.ejvs.2004.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Intrasac Pressure Waveforms After Endovascular Aneurysm Repair (EVAR) are a Reliable Marker of Type I Endoleaks, but not Type II or Combined Types: An Experimental Study

Abstract: Intrasac pressure waveforms following EVAR are easily defined following a type I endoleak. Waveforms obtained following type II endoleak simulation resemble the baseline waveform in an attenuated form. Intrasac pressures are, therefore, a reliable marker for type I, but not a type II endoleak. In the case of a combined endoleak, the type I endoleak waveform effectively masks that of the type II. Intrasac thrombus faithfully transmits intrasac pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…They demonstrated that the net effect of a type II endoleak is governed by the varying inlet branch pressure and that both types I and II endoleaks may elevate the sac pressure to aortic levels. Chaudhuri et al (2004) indicated that measuring the sac-pressure waveform after EVAR is an unreliable marker of type II endoleaks. Based on clinical data statistics, Fan et al (2001) confirmed that the sac branch vessel patency is associated with a significantly higher incidence of type II endoleaks after EVAR.…”
Section: Introductionmentioning
confidence: 98%
“…They demonstrated that the net effect of a type II endoleak is governed by the varying inlet branch pressure and that both types I and II endoleaks may elevate the sac pressure to aortic levels. Chaudhuri et al (2004) indicated that measuring the sac-pressure waveform after EVAR is an unreliable marker of type II endoleaks. Based on clinical data statistics, Fan et al (2001) confirmed that the sac branch vessel patency is associated with a significantly higher incidence of type II endoleaks after EVAR.…”
Section: Introductionmentioning
confidence: 98%
“…51 Although intrasac pressures and waveforms accurately revealed the presence of type I endoleak, they were unable to successfully define a pure type II endoleak.…”
Section: Other Experimental Models Of Type II Endoleakmentioning
confidence: 99%
“…There is also controversy regarding the role of thrombus in the sac in its potential to limit pressure transmission to the aneurysm wall. Thrombus has been observed to reduce sac and pulse pressure, but also to transmit systemic pressure to the aneurysm wall [2,11,13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%